Conocimientos sobre el manejo de la deshidratación en madres de niños menores de cinco años, usuarias del Subcentro de salud de Shell, de la provincia de Pastaza año 2013 - 2014 - López Rodríguez, Daysi Susana (2015)
This research concerns the knowledge management about dehydration that have mothers of children under five years old, users of health Subcentro Shell. It was made by reference to the population of Sacha Runa community with 30 mothers, given the high number of demand for treatment of diarrheas children who come to the clinic of Subcentro in a state of dehydration. Given this situation was proposed raise alternatives that influence the causes that are able to decrease the severity status of the arriving children to Subcentro, the design of this research is cross descriptive bibliographic fixed and field research, was used the survey and observation as techniques of data collection with its specific instruments, the data’s obtained during the research community study unveiled that 77% of mothers do not know the severity of the care required to avoid dehydration until reach the Subcentro . I was determined that 83% of mothers of children under five do not have the knowledge to control while avoiding diarrhea that may trigger dehydration. So a proposal was developed for training mothers on the primary management of dehydration in the home. With the completion of this work was intended to improve the level of knowledge and the rate of children with dehydration decrease. Keywords: Dehydration, management of dehydration, children under fiveyears